Application of Ijarah Contract in Gold Pawning Practices at the Sharia Bank - Gustiadi Herma Putra; M. Arif Musthofa; Hasnah Dewi; Kurniawan Kurniawan; Erwina Kartika Devi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to examine the implementation of the ijarah-based gold pawning product at Bank Syariah Indonesia (BSI) Jambi Branch, focusing on its operational procedures, appraisal process, and compliance with Sharia principles. Materials and methods. This research used a qualitative descriptive method, gathering primary data through in-depth interviews with branch officers and direct observation, supported by secondary data from official documents and relevant literature. Results. The findings reveal that BSI applies a multi-contract (uqud murakkabah) scheme consisting of rahn, qardh, and ijarah, in full compliance with Fatwa DSN-MUI No. 26/DSN-MUI/III/2002. Gold appraisal is carried out by certified appraisers using modern equipment and daily market price references. The ujrah fee is determined at the start of the contract and remains unchanged until maturity, ensuring fairness (al-‘adl) and legal certainty (al-yaqin). Security measures include a dedicated vault with a dual control system and the use of PWG Monitoring technology to enhance efficiency and accountability. However, some members of the public still misinterpret the ujrah fee as being equivalent to interest in conventional pawn systems, indicating the need for enhanced public education on Islamic financial principles. Conclusions. The ijarah-based gold pawning product at BSI Jambi Branch is proven to be an effective, secure, and Sharia-compliant financing solution, with strong potential to be developed further as an inclusive and sustainable Islamic financial instrument.